2008
DOI: 10.21836/pem20080116
|View full text |Cite
|
Sign up to set email alerts
|

Use of corticosteroid therapy on the modulation of uterine inflammatory response in mares after artificial insemination with frozen semen

Abstract: SummaryIn order to modulate uterine inflammatory response and evaluate the effect of corticosteroid therapy on fertility, 90 cycles of 45 mares were used for artificial insemination with frozen semen, using three different protocols: G1 -inseminated with frozen semen (800 x 10 6 viable spermatozoa pre-freezing) + 20 mL of seminal plasma; G2 -inseminated with frozen semen (800 x 10 6 viable spermatozoa pre-freezing) + corticosteroid therapy; G3 -inseminated with frozen semen (800 x 10 6 viable spermatozoa pre-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
(16 reference statements)
1
22
0
Order By: Relevance
“…The use of corticosteroids on the modulation of persistent post-breeding endometritis has been suggested to be a safe and effective treatment strategy for increasing fertility rates in susceptible mares (Dell'Aqua et al 2006, Bucca et al 2008, Papa et al 2008. As endometritis is a major economic problem to the equine industry, with one study finding that approximately 15% of Thoroughbred broodmares being susceptible to the development of persistent breeding-induced endometritis, there is an incentive to investigate more efficacious treatment strategies (Zent et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of corticosteroids on the modulation of persistent post-breeding endometritis has been suggested to be a safe and effective treatment strategy for increasing fertility rates in susceptible mares (Dell'Aqua et al 2006, Bucca et al 2008, Papa et al 2008. As endometritis is a major economic problem to the equine industry, with one study finding that approximately 15% of Thoroughbred broodmares being susceptible to the development of persistent breeding-induced endometritis, there is an incentive to investigate more efficacious treatment strategies (Zent et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, corticosteroids have been suggested to reduce uterine edema, intraluminal fluid accumulation, and have also been reported to improve fertility in selected mares with persistent breeding-induced endometritis (Dell'Aqua et al 2006, Bucca et al 2008, Papa et al 2008). We did not investigate the efficacy of treatment with dexamethasone on any of these parameters.…”
Section: Fig 2cmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is evidence that the judicious use of steroids may increase pregnancy rates in mares with endometritis Rohrbach et al, 2007;Bucca et al, 2008;Papa et al, 2008;Vandaele et al, 2010). Glucocorticoid therapy is a common medication to manage inflammatory diseases because of potent anti-inflammatory and immunosuppressive properties.…”
Section: Immunomodulators and Steroidsmentioning
confidence: 99%
“…Christoffersen et al (2012), observed that when dexamethasone was used in mares with experimental induced E. coli endometritis as an adjunctive treatment, fluid accumulation rarely occured. Oral administration of prednisolone (0.1 mg/kg) at 12-hour intervals for 4 days beginning 48 h before breeding, also improved pregnancy rates in mares susceptible to fluid accumulation (Papa et al, 2008). In contrast, administration of dexamethasone (10 or 20 mg i.m.)…”
Section: Immunomodulators and Steroidsmentioning
confidence: 99%